Autoimmune hemolytic anemia in chronic mucocutaneous candidiasis. - Oyefara, B I (1994)
Chronic mucocutaneous candidiasis is an immunodeficiency disease characterized by T-cell dysregulation and chronic superficial candidal infections. We report on three patients with chronic mucocutaneous candidiasis who developed autoantibodies to erythrocytes. Our first patient, a 19-year-old female, developed autoimmune hemolytic anemia (AIHA) that required multiple courses of treatment, including corticosteroids, intravenous immunoglobulin, and danazol. During the last exacerbation of AIHA, intensive treatment with corticosteroids and intravenous immunoglobulin failed and yet the patient responded to plasmapheresis. Our second patient, a 21-year-old male, developed AIHA which responded to oral corticosteroid therapy. Our third patient, a 6-year-old female without evidence of hemolysis, was found to have erythrocyte autoantibodies on routine screening. These three patients had positive direct antiglobulin tests, and the first patient had both immunoglobulin G (IgG) and IgM erythrocyte autoantibodies, while the remaining two patients had only IgG autoantibody. This is the first report of the association of AIHA with chronic mucocutaneous candidiasis. We suggest that all patients with chronic mucocutaneous candidiasis be screened periodically for erythrocyte autoantibodies. Plasmapheresis, a safe ancillary procedure in the management of AIHA, may be life-saving in some cases. The occurrence of erythrocyte autoantibodies in mucocutaneous candidiasis may be related to immunoregulatory disorders in this disease.